Bidirectional Relationship Between Sickle Cell Disease and Food Insecurity: Scoping Review - Faeben Wossenseged; Kristina Franklin; Talya Gordon; Ashley Buscetta; Gwenyth R. Wallen; Vence L. Bonham; Nicole Farmer (Health Equity)
Introduction: In the United States, sickle cell disease (SCD)—the homozygous inheritance of a point mutation within the beta-globin chain of hemoglobin—affects between 80,000 and 100,000 people. Adequate nutrition can influence the pathophysiology of SCD, and individuals with SCD who are undernourished are more likely to have impaired immune function and disease exacerbation. Undernourishment is often caused by food insecurity (FI), which is defined as “a household-level economic and social condition of limited or uncertain access to adequate food” by the USDA. FI disproportionately affects African Americans, a population disproportionately affected by SCD in the United States. Objectives: We performed a scoping review to better understand the relationship between FI and SCD severity. Methods: A comprehensive search for peer-reviewed research articles and meeting abstracts was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Selected studies were reviewed for descriptive analysis by three independent reviewers. Results: In total, 72 studies were identified, 62 were excluded for meeting inclusion criteria. The remaining 10 studies, 5 of which were meeting abstracts, were reviewed. Although limited evidence is available, the results of this scoping review suggest a bidirectional relationship between SCD and FI. Seven key themes were identified to help elucidate this relationship: 1) prevalence of FI among individuals with SCD, 2) child versus caregiver experiences of FI, 3) psychosocial factors, 4) food assistance benefits, 5) dietary intake, 6) external spending, 7) healthcare utilization. Conclusion: Findings from this scoping review suggest how SCD and FI work in tandem to exacerbate each other. Furthermore, the findings illustrate current gaps in the literature and opportunities for actions to address FI among individuals living with SCD.